A Comparative Study of Current and Potential Users of Mobile Payment Services - Chanchai Phonthanukitithaworn (2018)
© 2016, © The Author(s) 2016. Previous studies of mobile payment (m-payment) services have primarily focused on a single group of adopters. This study identifies the factors that influence an individual’s intention to use m-payment services and compares groups of current users (adopters) with potential users (non-adopters). A research model that reflects the behavioral intention to use m-payment services is developed and empirically tested using structural equation modeling on a data set consisting of 529 potential users and 256 current users of m-payment services in Thailand. The results show that the factors that influence current users’ intentions to use m-payment services are compatibility, subjective norms, perceived trust, and perceived cost. Subjective norms, compatibility, ease of use, and perceived risk influenced potential users’ intentions to use m-payment. Subjective norms and perceived risk had a stronger influence on potential users, while perceived cost had a stronger influence on current users, in terms of their intentions to use m-payment services. Discussions, limitations, and recommendations for future research are addressed.